Otoetnografi: Mempelajari Kasus Pribadi Peneliti - Semiarto Aji Purwanto (Antropologi Indonesia, 2011)
Ethnographic research is very close to case studies. Throughout its development, views and ways of doing ethnography experienced change. At first ethnography was merely describing ethnic groups as a case study which is done by making a detailed and objective description. In more recent time it became a description on a community which holds within it records of the researcher’s subjective experiences while searching for data in the field. There is a realization that cases that are presented through ethnography is by the researcher’s choice whether intentionally or not, even through compromise with an informant. The ethnography’s representational issues became stronger. Besides the realization of representation and authority in describing a community, discussions on modern-day ethnography is also filled with chosen cases that are more personal. Some experts offer the possibility of autoethnography as a choice in writing an ethnography. For the advocates, ethnography is able to bring up cases that have not been exposed by researchers from beyond the analyzed community. Autoethnography has become a way of articulating descriptions of the marginalized community. In the context of Indonesia, I see that autoethnography can be used as an offer towards the birth of claims of Indonesian anthropology. Keywords: autoethnography, case, representation, method